The Effect of Leadership Style on Student Achievement in the Digital Age - Annisa Annisa (CV. ADIBA AISHA AMIRA, 2022)
The development of student achievement in Madrasah Aliyah currently appears in the field is still relatively low. This phenomenon is expected to affect the level of public trust regarding services to meet student learning needs. The purpose of increasing the fulfillment of learning needs is to meet student satisfaction in madrasah aliyah which has an impact on learning achievement. This study uses a quantitative approach through a survey method. Research data on Madrasah Principal Leadership with teacher respondents and Teacher Teaching Performance, Madrasa Culture and Student Satisfaction with student respondents. Based on the hypothesis test, it was found that Madrasah Principal Leadership, Teacher Teaching Performance, Madrasa Culture simultaneously affect student satisfaction. This shows that an increase in one of the variables, namely the leadership of the madrasah principal or teacher teaching performance or madrasa culture will have an influence on increasing student satisfaction. Student satisfaction has an effect on learning achievement, reflecting that high and low learning achievement is influenced by student satisfaction. The recommendation of this research is to provide an alternative in increasing student satisfaction and its impact on learning achievement